Building methodological bridges - Bergh, Donald D.; Ketchen, David J. (Bingley, U.K. : Emerald, 2011)
This book series mission is to provide a forum for critique, commentary, and discussion about key research methodology issues in the strategic management and general management literatures. These research streams rely on an array of complex methods drawn from various allied disciplines to examine how managers attempt to lead their firms toward success. The overall management field is undergoing a rapid transformation in methodological rigor, and researchers face many new challenges ahead about how to conduct their research and in understanding the implications that are associated with their choices. This book series seeks to bridge the gap between what researchers know and what they need to know about methodology. In each volume, renowned scholars contribute chapters in their areas of methodological expertise.
Introduction : building methodological bridges / Donald D. Bergh, David J. Ketchen -- Rediscovering the individual in strategy : methodological challenges, strategies, and prospects / Steven W. Floyd, Rebekka Sputtek -- Into the great wide open : bridging the micro-macro divide in the organizational sciences / M. Ronald Buckley, Maria Riaz Hamdani, Anthony C. Klotz, Sorin Valcea -- Strategic human resource staffing and organization research : are they one-size-fits-all endeavors? / Philip Bobko, Denise Potosky -- Leader-member exchange (LMX) measurement : evidence for consensus, construct breadth, and discriminant validity / Dana L. Joseph, Daniel A. Newman, Hock-Peng Sin -- Entrepreneurial mobility / Mike Wright -- Multi-study packages in organizational science research / Wayne A. Hochwarter, Gerald R. Ferris, T. Johnston Hanes -- Templates and turns in qualitative studies of strategy and management / Ann Langley, Chahrazad Abdallah -- The revolution with a solution : all is not quiet on the statistical and methodological myths and urban legends front / Robert J. Vandenberg -- Qualitative comparative analysis and strategic management research : current state and future prospects / Thomas Greckhamer, Kevin W. Mossholder -- Worth a thousand words : photographs as a novel methodological tool in strategic management / Joshua L. Ray, Anne D. Smith.
Keywords: Research -- Methodology; Business planning; Strategic planning